The Production of Religious Space: Lived Space and the Sacred-Economic Dialectic in the Sunan Ampel Pilgrimage Area, Surabaya - Azizah, Siti; Karnaji, Karnaji; Suyanto, Bagong (Islamica: Jurnal Studi Keislaman, 2026)
This study examines the production of religious space in the Sunan Ampel area of Surabaya through a sociological-historical approach, emphasizing the concept of lived space and the dialectics between sacrality and economy. Departing from Henri Lefebvre’s theory of space production, this article argues that the sacredness of Ampel is not a static entity that is inherited ahistorically, but rather the result of social construction that continues to be produced and reproduced through ritual practices, social relations, economic activities, and collective memory that are formed historically. This research uses a qualitative method with in-depth interviews, field observations, and historical document analysis. The study’s findings show that, sociologically and historically, Ampel evolved from a religious settlement into an urban religious pilgrimage and tourism area with layers of symbolic, social, and economic meaning. The dialectic between sacredness and economics does not exist as a structural conflict of a binary nature, but rather as an everyday social experience negotiated by the actors. In the Sunan Ampel lived space, economic activities are tied to religious ethics and the moral economy, thereby supporting the sacred space’s sustainability. Keywords: space production, lived space, sacrality, economy